2019
DOI: 10.1136/bmjopen-2019-032763
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of not smoking during pregnancy for Australian Aboriginal and Torres Strait Islander women and their babies: a retrospective cohort study using linked data

Abstract: ObjectivesTo provide evidence for targeted smoking cessation policy, the aim of this study was to compare pregnancy outcomes of Aboriginal mothers who reported not smoking during pregnancy with Aboriginal mothers who reported smoking during pregnancy.DesignPopulation based retrospective cohort study using linked data.SettingNew South Wales, the most populous Australian state.Population18 154 singleton babies born to 13 477 Aboriginal mothers between 2010 and 2014 were identified from routinely collected New So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…As shown in previous research, active and passive maternal smoking during pregnancy increases the risk of having a child with low birth weight [27,34] and significantly increases other negative pregnancy outcomes, such as preterm birth [17,21], respiratory distress [1], antepartum and intrapartum stillbirth [5], perinatal death [24], long-term morbidity in offspring [32], and sudden unexpected infant death [3].…”
Section: Introductionmentioning
confidence: 66%
“…As shown in previous research, active and passive maternal smoking during pregnancy increases the risk of having a child with low birth weight [27,34] and significantly increases other negative pregnancy outcomes, such as preterm birth [17,21], respiratory distress [1], antepartum and intrapartum stillbirth [5], perinatal death [24], long-term morbidity in offspring [32], and sudden unexpected infant death [3].…”
Section: Introductionmentioning
confidence: 66%
“…2 A strong association between maternal smoking during pregnancy and stillbirth has been reported. [3][4][5] Although associations have been found for maternal drinking during pregnancy and abortion, being small for gestational age, and stillbirth, [6][7][8] the association with stillbirth may be limited to binge drinking. 9 Previous studies 9,10 that assessed the association between stillbirth and maternal drinking or smoking have often been retrospective and have inadequately classified quantity, frequency, and timing of exposures.…”
Section: Introductionmentioning
confidence: 99%
“…With both programs having an important element of a reduction in pregnant women smoking, renewed attention on smoking cessation in pregnancy is timely. A recent study of 18 154 singleton babies born to Aboriginal mothers residing in NSW found that 20% of stillbirths and 26% of preterm births were attributable to smoking in this population, as well as 30% of neonatal deaths and 48% of small for gestational age births 21 . Among this population 51% of women reported smoking; however, in order to comply with our ethics requirements for this study, we were unable to separately enumerate smoking rates for Aboriginal mothers.…”
Section: Discussionmentioning
confidence: 94%
“…These concerns were echoed in interviews with young pregnant women in Western Australia who said that being surrounded by smokers made it difficult to stop, and had worries about being excluded from their social sphere if they quit 24 . Although data were not available from this study for Aboriginal people, it is known that smoking rates among Aboriginal mothers are higher than the general population 21 . Effective interventions, especially for the subgroups of women identified as being more likely to smoke during pregnancy, are required.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation